Leaf anatomical traits corroborate the leaf economic spectrum: a case study with deciduous forest tree species - Somavilla, Nadia Silvia; Kolb, Rosana Marta [UNESP]; Rossatto, Davi Rodrigo [UNESP] (Soc Botanica Sao Paulo, 2014)
Deciduous forests are seasonal systems that occur scattered throughout the Neotropics. Many aspects about these ecosystems have been studied. However, there is a lack of information about leaf structure and its possible functional and adaptive aspects. Here we examined leaf anatomy and specific leaf area (SLA) in 13 dominant tree species of dry forests in central Brazil, identifying structural patterns of these species. As the system is seasonal, with species presenting a deciduous behavior, we expect to find tree species with a set of mesomorphic leaf traits. The studied dry forest trees share similar leaf structure, with one-layered adaxial and abaxial epidermis and a well-developed mesophyll, high values of SLA, and the presence of calcium crystals and mucilaginous cells. Higher values of SLA and the high investment achieved in the mesophyll (especially in parenchyma tissue) are probably related to the accomplishment of a high performance of carbon and nutrients gain during the limited wet season.
Keywords: Calcium crystals; Deciduousness; Dry forest; Leaf traits; Mucilage